The Relational Primacy in Electoral Persuasion: Comparative Analysis of Interpersonal Communication, Credibility, and Voter Choice in the 2022 Osun and Ekiti Gubernatorial Elections - Akinyemi-Oke, Alaba Victoria (African Journal of Stability and Development (AJSD), 2024)
Political communication is central to contemporary electoral democracy, yet its effectiveness varies considerably across different socio-political environments. In Nigeria, where trust in institutions and mass media remains fragile, the persuasive force of election campaigns is shaped less by media visibility and more by the relational dynamics embedded in everyday social life. This study critically examines the 2022 Osun and Ekiti gubernatorial elections to determine the comparative influence of mass-mediated and interpersonal communication on two core electoral outcomes: candidate credibility and voter choice. Drawing on a cross-sectional survey of 397 registered voters, analysed using descriptive statistics, Pearson correlation and chi-square tests, the study reveals a decisive hierarchy of influence in which interpersonal communication, particularly word-of-mouth, personal recommendations, and community-based opinion leadership significantly outperforms impersonal strategies such as billboards, advertising, and broadcast media. Findings demonstrate that although mass media achieved high exposure, it failed to secure a proportional persuasive impact. Instead, credibility judgments and voting decisions were overwhelmingly mediated by trusted social ties. These results align with and extend the Two-Step Flow and Persuasion models by showing that, in low-trust political settings, mass-mediated messages require interpersonal validation to translate into behavioural action. The study contributes to African political communication scholarship by articulating a relational model of electoral persuasion and offers practical recommendations for designing trust-centred, community-anchored campaign strategies.